영·한 통번역 교육을 위한 클리셰(cliche) 분석 : 셰익스피어 극 텍스트를 중심으로 - 유선영; You, Seon-Young (한국콘텐츠학회 논문지, 15(11), 2015)
The purpose of this study was to analyze the cliche for English-Korean interpretation and translation training with special reference to the cliche based on Shakespeare's works texts. The term of 'idioms' are generally used as figurative expressions instead of the term of 'cliche'. Thus, cliches must be reinterpreted in the lexicon that are used in useful expressions. Cliches are often idioms. Idioms are figurative phrases with an implied meaning; the phrase is not to be taken literally. This causes difficulty when translating to another language because the meaning may not be understood by people within that culture. Cliches are figurative or literal expressions and are overused expressions. Consequently, the cliches are distinguished from the idioms by the transparent meanings. This study was examined based on the cliches shown in Shakespeare's works texts. After all, anyone who wants to become an efficient English learners, interpretor and translator should be familiar with cliches. They had better use the cliche in English learning site. I hope this study will be helpful even a bit to his attempt. 이 연구는 그 중요성이 인식되지 못하고 깊이 있는 연구가 행해지지 않았던 클리셰(cliche)에 주목하여, 셰익스피어 극에 나타난 클리셰를 분석하고자 했다. 일반적으로 클리셰는 은유의 특성을 가진 관용어로만 여겨져 주목받지 못했으나, 은유라는 인지 기제를 갖춘 언어 표현으로써 관용어를 포함한 광의의 개념이다. 본 연구는 영어에서 클리셰의 개념과 범주를 명확히 하기 위해 먼저 클리셰의 개념과 관용어와의 차이점을 살펴보았다. 아울러 본 연구는 클리셰에 대한 깊이 있는 이론적 논의의 출발점이 되고자 하는 취지에서 영문학 작품의 비조이자 클리셰가 가장 많이 언급된 셰익스피어의 작품을 분석 대상으로 삼아, 셰익스피어의 총 20개의 작품에 나타난 클리셰 분석을 통해 셰익스피어의 작품 속에 쓰인 클리셰가 관용어로만 규정지어 질 수 없음을 증명하고자 했다. 본 연구는 클리셰를 셰익스피어의 작품을 통해 정리하여 실증적으로 분석함으로써 관용어와 클리셰의 개념을 명확히 함과 동시에, 두 용어의 사용에 기준을 마련하고, 클리셰를 효율적으로 이해하고 사용할 수 있도록 발판을 마련했다는 점에서 영어 학습자를 비롯한 영 한 통번역 교육 분야의 연구 확장에 기여할 것으로 기대한다.